Didactique littéraire - Diaz, Olga (Wydawcnictwo Naukowe UAM, 1990)
Language and literature have always shown a fundamental unity in what we could call the art of writing. Formally, the establishment of any literary praxis should therefore lead towards an improvement in the construction of language. In fact, we cannot separate linguistic valorisation from the cultural process in reading and writing which are characterised by cognition and creativity. And that is why we are talking at the same time about the study of texts and the study of writing.